Measles outbreak, Montenegro January–July 2018: Lessons learned. Issue 2 (11th October 2021) - Mugoša, Boban; Ceccarelli, Giancarlo; Begić, Senad; Vujošević, Danijela; Zekovic, Zeljka; Ciccozzi, Massimo; Vratnica, Zoran
Abstract: In 2017, the Regional Verification Commission for Measles and Rubella Elimination (RVC) of the World Health Organization confirmed that measles elimination was sustained in Montenegro, and the previous endemic transmission remained interrupted. However, the RVC was extremely concerned over the continuing low vaccination coverage reported for this country. In this study, we describe the most recent measles epidemic in Montenegro using the epidemiological data collected from January 1 to July 31, 2018. The outbreak is largely attributable to a dangerous accumulation of susceptible subjects across the country and represents a high‐risk factor for re‐establishing endemic transmission in the Balkan area. This study showed how a vaccine‐preventable communicable disease outbreak can have a dramatic impact and severe consequences on regional public health system performance in terms of the sanitary spending point of view. A detailed update is provided on the epidemiological situation in this Central European area, not available until now. Highlights: On 2017, the Regional Verification Commission for Measles and Rubella Elimination (RVC) of World Health Organization confirmed that measles elimination was sustained in Montenegro, and the previous endemic transmission remained interrupted. The reduction in vaccination coverage was one of the main causes of the measles outbreak in Montenegro in 2018: this report provides information on the impact of the epidemic on the national health service and complements the gap in epidemiological data on measles trends available for this country of the WHO European Region.